The focus of academic economics: Before and after the crisis - Ernest Aigner; Matthias Aistleitner; Florentin Glötzl; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2018)
Has the global financial crisis of 2007ff had a visible impact on the economics profession? To answer this question we employ a bibliometric approach and compare the content and orientation of economic literature before and after the crisis with reference to two different samples: A large-scale sample consisting of more than 440,000 articles published between 1956 and 2016 and a smaller sample of 400 top-cited papers before and after the crisis. Our results suggest that - unlike the Great Depression of the 1930s - the current financial crisis did not lead to any major theoretical or methodological changes in contemporary economics, although the topic of financial instability received increased attention after the crisis.
Keywords: A14; B20; B26; G01; N00; N01; 330; crisis; economics profession; economic journals; keyword analysis; paradigmatic development